Match the Product

P = k = 0 m 1 [ m ( m + 1 ) 2 T k ] \large P = \prod_{k=0}^{m-1}\left[m(m+1)-2T_k\right]

where T k T_k is the k k th triangular number and m = n 2 m=\left \lceil \dfrac n2 \right \rceil

Then P P equals which of the following:

  1. 2 x = 0 m 1 ( m 2 x 2 ) \displaystyle 2\prod_{x=0}^{m-1}(m^2-x^2) for odd n n
  2. 2 n ! 2n!
  3. 2 x = 0 m 1 ( m 2 x 2 ) \displaystyle 2\prod_{x=0}^{m-1}(m^2-x^2) for even n n
  4. n ! n!

Notations:

  • T k = k ( k + 1 ) 2 T_k=\dfrac {k(k+1)}2 , where k k is a non-negative integer, denotes the triangular numbers 0,1,3,6,10,15....
  • \lceil \cdot \rceil denotes the ceiling function .
Both 1 and 3 Only 2 Both 2 and 3 Only 3 Both 2 and 4 Only 1 Only 4

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mark Hennings
Jul 12, 2017

We have P = k = 0 m 1 ( m ( m + 1 ) 2 T k ) = k = 0 m 1 ( m ( m + 1 ) k ( k + 1 ) ) = k = 0 m 1 ( m k ) ( m + k + 1 ) = k = 0 m 1 ( m k ) k = 0 m 1 ( m + k + 1 ) = m ! × ( 2 m ) ! m ! = ( 2 m ) ! = { n ! n even ( n + 1 ) ! n odd \begin{aligned} P & = \prod_{k=0}^{m-1} \big(m(m+1) - 2T_k\big) \; = \; \prod_{k=0}^{m-1}\big(m(m+1) - k(k+1)\big) \\ & = \prod_{k=0}^{m-1}(m-k)(m+k+1) \; = \; \prod_{k=0}^{m-1}(m-k) \prod_{k=0}^{m-1}(m+k+1) \\ & = m! \times \frac{(2m)!}{m!} \; = \; (2m)! \; = \; \left\{ \begin{array}{ll} n! & n \mbox{ even} \\ (n+1)! & n \mbox{ odd} \end{array} \right. \end{aligned}

Thus options ( 2 ) (2) and ( 4 ) (4) are not always true. On the other hand Q = 2 x = 0 m 1 ( m 2 x 2 ) = 2 x = 0 m 1 ( m x ) ( m + x ) = 2 × m ! × ( 2 m 1 ) ! ( m 1 ) ! = 2 m × ( 2 m 1 ) ! = ( 2 m ) ! \begin{aligned} Q & = 2 \prod_{x=0}^{m-1} (m^2 - x^2) \; = \; 2\prod_{x=0}^{m-1} (m-x)(m+x) \\ & = 2 \times m! \times \frac{(2m-1)!}{(m-1)!} \; = \; 2m\times (2m-1)! \; = \; (2m)! \end{aligned} for all n 1 n \ge 1 .

The answer should be ( 1 ) and ( 3 ) \boxed{(1) \mbox{ and } (3)} .

Thank you for an excellent solution

Mrigank Shekhar Pathak - 3 years, 11 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...